A Cross-sectional study to assess the Level of knowledge of Youths aged 18-35 regarding negative Consequences of Cigarette smoking at Napier market, Jinja City. - Moses Hajusu Mangeni; Sam Wanyonyi; Boniface Ogwok; Harriet Anamo; Edmond Okello; Michael Albert Olinga (Student's Journal of Health Research, 2022)
Background: Cigarette smoking is on the increase among youths, especially in developing countries, and is a leading cause of premature morbidity and mortality worldwide. Youths incorrectly perceive that cigarette smoking is less risky than other behaviors such as alcohol consumption and drug use. The purpose of this study is to assess the determinants of cigarette smoking among youths in Napier market, Jinja city Methodology: A cross-sectional descriptive study design employing both quantitative and qualitative methods of data collection was employed. 30 respondents were selected using a convenient non-probability sampling method and data was collected using semi-structured questionnaires. Results: Regarding knowledge of the dangers of cigarette smoking Majority of the respondents had heard about the dangers of cigarette smoking (80%). Commonly mentioned dangers of cigarette smoking included lung cancer (70%), mouth cancer (36%), heart diseases (30%), hypertension (32%), and stroke (22%). Sources of information were radios (64%) and peers (17%). Of the 57% of the respondents that were willing to quit, 74% did not know the exact time at which they hoped to quit cigarette smoking Conclusion: Respondents' related factors associated with smoking were lack of employment (66%) non involvement in religious activities (66%) negative life experiences (63%), having a smoking friend (43%), and having smoking parents (36%) Recommendation: Although the majority of respondents had heard about the dangers of cigarette smoking, the majority scored below average on common dangers of cigarette smoking and the majority were not sure of when to quit the smoking habit, therefore there is an urgent need to create awareness about the specific dangers associated with cigarette smoking, the transient nature of its perceived benefits and the fact that the risks associated with smoking are severe.